2010
DOI: 10.3989/scimar.2010.74n2223
|View full text |Cite
|
Sign up to set email alerts
|

Diet, growth and reproduction of four flatfishes on the Portuguese coast

Abstract: from commercial fishing vessels operating with gill nets and bottom trawls along the Portuguese coast in order to examine feeding habits, age and growth and reproduction. Citharus linguatula (Linnaeus, 1758), Lepidorhombus boscii (Risso, 1810) and Microchirus azevia (de Brito Capello, 1867) fed mainly on crustaceans, whereas Platichthys flesus (Linnaeus, 1758) fed mainly on echinoderms and crustaceans. Feeding activity was highest in spring and summer; females and small individuals showed the lowest vacuity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
7
24
2
5
Order By: Relevance
“…The differences in the growth rate between the male and female four-spotted megrim were also observed by Fuertes (1978), Bello & Rizzi (1987), Castilho et al (1993), Santos (1994), Landa et al (2002) and Teixeira et al (2010). Similarly, our findings indicated that female four-spotted megrims were larger than the males.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The differences in the growth rate between the male and female four-spotted megrim were also observed by Fuertes (1978), Bello & Rizzi (1987), Castilho et al (1993), Santos (1994), Landa et al (2002) and Teixeira et al (2010). Similarly, our findings indicated that female four-spotted megrims were larger than the males.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, the age class of the four-spotted megrims ranged between 1 and 13 ages. Castilho et al (1993), Vassilopoulou & Ondrias (1999), Robson et al (2000), Bostanci & Polat (2008) and Teixeira et al (2010) reported the longevity limits as 0-12, 0-8, 4-11, 3-8 and 2-9 ages, respectively. Nash & Geffen (2005) stated that the reasons of differences in longevity could be attributed to latitudinal differences as well as to the effects of temperature, intensities of competition for food, food availability, life history strategies and fishing efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La información publicada sobre esta especie se refiere sólo a su crecimiento a lo largo de la costa occidental de Bretaña (Deniel 1990), en el estuario del Tajo (Dinis 1986) y en la costa portuguesa (Teixeira et al 2009), y a su reproducción en la costa occidental de Bretaña (Deniel et al 1989) y en el archipiélago canario (Pajuelo y Lorenzo 2008). Aunque P. lascaris es una especie de interés comercial creciente en Portugal (Teixeira et al 2009(Teixeira et al , 2010 y es la especie objetivo más importante en la pesquería artesanal de peces planos de Canarias (Pajuelo y Lorenzo 2008), la biología y la dinámica de sus poblaciones son prácticamente desconocidas. En el archipiélago canario, P. lascaris se captura conjuntamente con otras especies de lenguado de interés comercial con redes de enmalle, pero no se dispone de datos relativos a las capturas ni al nivel de explotación.…”
Section: Methodsunclassified
“…The only published information relates to growth aspects of the species along the west coast of Brittany (Deniel 1990), the Tagus Estuary (Dinis 1986), and the Portuguese coast (Teixeira et al 2009), and to its reproductive biology on the west coast of Brittany (Deniel et al 1989) and in the Canarian Archipelago (Pajuelo and Lorenzo 2008). Although P. lascaris is a species of commercial interest on the Portuguese coast (Teixeira et al 2009(Teixeira et al , 2010, and it is the most important flatfish species targeted by small-scale fisheries off the Canary Islands (Pajuelo and Lorenzo 2008), little is known about its life history or population dynamics. Around the Canaries, P. lascaris is fished together with other commercially important sole species using gill nets, but no records of the total catches, or level of fishing, exist.…”
Section: Introductionmentioning
confidence: 99%